The Evolution of Business Ethics in China and the United States: Convergence, Divergence, or Crossvergence?. (August 2022) - Lee, Jong Min; Paik, Yongsun; Vance, Charles; Li, Donghong; Groves, Kevin
ABSTRACT: This study presents a cross-temporal comparison of managerial ethics in China and the US. Although it is well established that cross-cultural differences exist in business ethics and that culture and values in a society may evolve over time, little attention has been paid to the longitudinal changes in such cross-cultural differences that might have occurred over time. Building on three different perspectives on values evolution, namely, convergence, divergence, and crossvergence, we investigate whether and how cross-cultural differences in managerial ethical decision-making and the associated moral philosophy have changed in China and the US over the decade between the mid-1990s and the mid-2000s. Our analysis reveals that the difference in Chinese and American managers' ethical decision-making evolved in many different directions over the decade, lending support to the crossvergence perspective. Interestingly, however, we discover that the divergence outlook prevails when it comes to the moral philosophies behind their decision-making. These findings provide critical insights into cross-cultural as well cross-temporal evolution in business ethics in a world of increasing cross-cultural and multicultural interactions. 摘要: 本文对中美两国经理人员的商业伦理决策进行了跨期比较研究。已有研究普遍认为，商业伦理中存在着跨文化差异，且一个社会的文化和价值观会随着时间的推移而演化。但是，相关研究对这种跨文化差异随着时间的推移而发生纵向变化的关注相对较少。基于价值观演化的三种不同视角——趋同、趋异和交叉融合，我们研究了在20世纪90年代中期至21世纪最初十年的中期这一阶段，中美两国经理人员的商业伦理决策和相关道德哲学的跨文化差异的纵向变化。我们的分析表明，在这十年中，中美两国经理人员的商业伦理决策差异在多个不同方向上演化，存在着交叉融合。然而，有趣的是，我们也发现，当涉及到商业伦理决策背后深层次的道德哲学时，相互间的差异点占了上风。这些发现为在全球日益增多的跨文化和多元文化互动中深度认识商业伦理的跨文化和跨时间演化提供了重要见解。